Gifting the other, or why are nineteenth-century German bourgeois men acting like Trobriand Islanders? - Geller, Jay (Critical research on religion, 2013)
Taking its lead from analyses of gift exchange by Marcel Mauss and Marshall Sahlins as well as of contact by Charles Long and Jonathan Z Smith, this article elaborates a theory of the exchange, among dominant social subjects, of representations of their subjected proximate others in order to rectify the crisis precipitated by contact with otherness that threatens their claims to autonomy, authority, homogeneity, and universality. Specifically it situates the polemical exchange of representations of women among Friedrich Schlegel (Lucinde/Lucinde), G W F Hegel (Antigone/Phenomenology of Spirit), and Karl Gutzkow (Wally/Wally the Skeptic) as exemplary German male bourgeois efforts to rectify the crises to subject formation generated, in part, by the emergence of gender-coded bifurcated bourgeois society and signaled by the Kantian and French Revolutions. The public dissemination of apotropaic representations screened the dependence upon proximate others by, and determined the positions among, exchange participants as well as maintained structures of domination.